Research forum: “developing shariah-compliant fertility treatment guideline for muslim patients” - Munira, Abdul Razak (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
7 November 2012. A research forum: “Developing Shariah-Compliant Fertility Treatment Guideline for Muslim Patients” was initiated by a research team collaboration of two universities namely Universiti Malaysia Pahang (UMP) and the International Islamic University Malaysia (IIUM) at the Conference Room, UMP Library.